2021
DOI: 10.1002/agm2.12186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors contributing to primary sarcopenia in relatively healthy older Indians attending the outpatient department in a tertiary care hospital: A cross‐sectional study

Abstract: Background Literature is scarce on primary sarcopenia among Indian older adults. This study was aimed to estimate the prevalence of primary sarcopenia among older persons in India using the European Working Group on Sarcopenia in the Older People 2010 (EWGSOP) diagnostic criteria and to elucidate the factors leading to its development. Methodology Two hundred twenty‐seven subjects over 60 years of age attending the geriatric outpatient clinic were recruited for the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…The prevalence of sarcopenia can be influenced by many factors, including race and age. In China, the prevalence of sarcopenia in individuals aged 60 is 10.6%, with 11.3% in men and 9.8% in women, 9.3% in men and 4.1% in women in Taiwan, and 9.4% among elderly male community dwellers in Hong Kong ( 22 , 23 ). Older adults with stroke have an accelerated loss in muscle mass and strength compared with those without stroke ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sarcopenia can be influenced by many factors, including race and age. In China, the prevalence of sarcopenia in individuals aged 60 is 10.6%, with 11.3% in men and 9.8% in women, 9.3% in men and 4.1% in women in Taiwan, and 9.4% among elderly male community dwellers in Hong Kong ( 22 , 23 ). Older adults with stroke have an accelerated loss in muscle mass and strength compared with those without stroke ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1 . Five cross-sectional studies [ 31 , 32 , 33 , 34 , 35 ], one longitudinal study [ 36 ], and one case-control study [ 37 ] that investigated 3353 community-dwelling older adults with a mean age of approximately 73 years from Australia, Belgium, Finland, India, and the Netherlands were included. One study [ 32 ] included participants from Italy, Poland, the Netherlands, and the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment scores are shown in Supplementary Material S3 . The overall score of cross-sectional studies [ 31 , 32 , 33 , 34 , 35 ] ranged from six to seven. All of the studies clearly stated the research question (item 1), specified the study population (item 2), recruited participants from the same or a similar population (item 4), clearly defined and used valid and reliable exposure (item 9) and outcome (item 11) measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations